Experience With the Use of the MicroDTTect Device for the Diagnosis of Low-Grade Chronic Prosthetic Joint Infections in a Routine Setting - Kolenda, Camille; Josse, Jérôme; Batailler, Cécile; Faure, Allison; Monteix, Alice; Lustig, Sébastien; Ferry, Tristan; Laurent, Frédéric; Dupieux, Céline (Frontiers in Medicine, 2021)
Background. In prosthetic joint infections (PJIs), identification of the causative microorganisms is critical to successfully adapt and optimize treatment. However, microbiological diagnosis of PJIs remains a challenge notably because bacteria are embedded in biofilm adhered to the prosthetic material. Recently, dithiothreitol (DTT) treatment of prosthesis has been proposed as a new strategy to release bacteria from biofilm and to improve the yield of microbiological diagnosis. In this study, we evaluated the interest of a commercial device using DTT, the MicroDTTect system (Heraeus, Hanau, Germany), for the diagnosis of low-grade chronic PJIs, compared to the conventional culture of periprosthetic tissue (PPT) samples. Methods. Twenty patients undergoing a surgery procedure for removal of prosthetic material because of a suspicion of low-grade PJI without pre-operative microbiological documentation were included (NCT04371068). Bacteriological results using the fluid obtained after prosthesis treatment with the MicroDTTect system were compared to results obtained with conventional culture of PPT samples. Results. All the bacteria considered as responsible for PJIs recovered from culture of PPT samples were also detected using the MicroDTTect device. For one patient, an additional bacterial isolate (Staphylococcus haemolyticus) suspected to be involved in a polymicrobial PJI was identified using DTT treatment. Time to positivity of the cultures was also reduced using the MicroDTTect system, notably in case of Cutibacterium acnes infection. However, probable bacterial contaminants were found (MicroDTTect system, n=5; PPT samples, n=1). Conclusion. This study showed that DTT treatment of the prosthetic component using the MicroDTTect device could improve the microbiological diagnosis of low-grade PJIs.